2023
DOI: 10.3390/medicina59081468
|View full text |Cite
|
Sign up to set email alerts
|

Impulse Control Disorders in the Polish Population of Patients with Parkinson’s Disease

Abstract: Background and Objectives: Parkinson’s disease (PD) is one of the most common neurodegenerative diseases in the world. It is characterized by the presence of not only typical motor symptoms but also several less known and aware non-motor symptoms (NMS). The group of disorders included in the NMS is Impulse Control Disorders (ICDs). ICDs are a group of disorders in which patients are unable to resist temptations and feel a strong, pressing desire for specific activities such as gambling, hypersexuality, binge e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 68 publications
1
1
0
Order By: Relevance
“…Impulse Control Disorders (ICDs) including pathological gambling, hypersexuality, compulsive eating, compulsive buying, and other related behaviors are NMSs of PD. A prospective study by Toś et al [7] found a prevalence of 27.41% in Polish PD patients, which is comparable to other European populations. The risk factors for developing ICDs include a longer duration of the disease, motor complications, sleep disorders, and the use of DA and L-dopa.…”
Section: An Overview Of Published Articlessupporting
confidence: 54%
“…Impulse Control Disorders (ICDs) including pathological gambling, hypersexuality, compulsive eating, compulsive buying, and other related behaviors are NMSs of PD. A prospective study by Toś et al [7] found a prevalence of 27.41% in Polish PD patients, which is comparable to other European populations. The risk factors for developing ICDs include a longer duration of the disease, motor complications, sleep disorders, and the use of DA and L-dopa.…”
Section: An Overview Of Published Articlessupporting
confidence: 54%
“…This study covered a cohort of Polish patients with idiopathic Parkinson's disease (PD) from the study by Toś et al [17], extended with additional patients-a total of 185 patients with PD and 35 patients with atypical parkinsonian syndromes (27 with PSP and 9 with MSA) consecutively enrolled in the study from November 2020 to June 2023. The inclusion criteria were as follows: (a) informed and voluntary consent to participate in the study; (b) clinical diagnosis of one of the parkinsonian syndromes: PD, according to the Movement Disorder Society Clinical Diagnostic Criteria for Parkinson's disease [18], clinically established MSA or clinically probable MSA according to the Movement Disorder Society Criteria for the Diagnosis of Multiple System Atrophy [19], and clinically probable PSP or clinically possible PSP according clinical diagnosis of progressive supranuclear palsy based on the Movement Disorder Society criteria [20]; (c) the motor and cognitive patient's condition enabled the completion of the questionnaire.…”
Section: Subjects and Data Collectionmentioning
confidence: 99%